MIKE's PET: A participant-based experiment tracking tool for HCI practitioners using mobile devices - Mohamedally, Dean; Edlich, Stefan; Klaus, Enrico; Zaphiris, Panayiotis (My University, 2006)
Knowledge Elicitation (KE) methods are an integral part of Human Computer Interaction (HCI) practices. They are a key aspect to the synthesis of psychology empirical methods with requirements engineering, User Centred Design (UCD) and user evaluations. Examples of these methods include prototyping, focus groups, interviews, surveys and direct video observation. The MIKE project (Mobile Interactive Knowledge Elicitation) at the Centre for HCI Design, City University London, UK provides mobile cyberscience capabilities for HCI practitioners conducting such research while at stakeholder locations. This paper reports on the design and development of a new MIKE based tool, named PET, a Participant-based Experiment Tracking tool for HCI practitioners using Java-based (J2ME) mobile devices. PET integrates its user tracking techniques with the development of the second generation implementation of the CONKER (COllaborative Non-linear Knowledge Elicitation Repository) Web Service. We thus report further on CONKER v2.0s new capabilities developed to enable tighter collaboration and empirical data management between HCI practitioners, considering their UCD needs. The visualisation, tracking and recording of HCI participant-based datasets via PET is explored with close connectivity with the CONKER v2.0 Web Service, in order to provide mobile-web cyberscience for remote and local HCI practitioners.
Keywords: HCI; Mobile Interactive Knowledge Elicitation; Web-Portals; Mobile Cyberscience